2018
DOI: 10.1002/jcu.22603
|View full text |Cite
|
Sign up to set email alerts
|

Can point shear wave elastography differentiate focal nodular hyperplasia from hepatocellular adenoma

Abstract: PurposeFocal nodular hyperplasia (FNH) and hepatocellular adenoma (HCA) are liver tumors that require different management. We assessed the potential of point shear wave elastography (pSWE) to differentiate FNH from HCA and the interobserver and intraobserver reliability of pSWE in the examination of these lesions and of native liver tissue (NLT).MethodsThe study included 88 patients (65 FNH, 23 HCA). pSWE was performed by two experienced liver sonographers (observers 1 [O1] and 2 [O2]) and acquired within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…As a result, the measurement results may show discrepancies. Taimr 27 reported that elements such as the tumor margin, the presence of a capsule, and heterogeneity in the internal echo may appear as artifacts in SWM. Artifacts in the SWM of solid mass lesions have been reported to include capsule reverberation artifacts, penetration limitations or dropout artifacts, artifacts due to blood vessels, shadowing artifacts, tissue motion artifacts, and near‐field distortion/precompression artifacts 28–30 .…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the measurement results may show discrepancies. Taimr 27 reported that elements such as the tumor margin, the presence of a capsule, and heterogeneity in the internal echo may appear as artifacts in SWM. Artifacts in the SWM of solid mass lesions have been reported to include capsule reverberation artifacts, penetration limitations or dropout artifacts, artifacts due to blood vessels, shadowing artifacts, tissue motion artifacts, and near‐field distortion/precompression artifacts 28–30 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the EUS-SWM system yielded a low reliability index (VsN) or measurement failure for extremely hard lesions with a heterogeneous structure such as fibrosis in a tumor. Various artifacts have been reported to appear due the position of the measurement ROI, effects of precompression by the probe, motion effect of the target lesion, and the heterogeneity in the focal mass of the lesion, with regard to hardness quantification via SW-EG [3742].…”
Section: Discussionmentioning
confidence: 99%
“…Using this difference, we can differentiate HCA from FNH, despite it being atypical. Ultrasound elastography, which has become more popular in the recent years, also recognizes FNH as a stiffer mass than HCA, as in this case [ 5 ]. However, as mentioned above, MRE is more useful than ultrasound elastography because it can be used simultaneously for HCC screening and staging in Gd-EOB-DTPA-enhanced MRI.…”
Section: Discussionmentioning
confidence: 99%